2005
DOI: 10.1097/01.jps.0000157814.29792.f2
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal Branch of the Supraorbital Nerve and Temporal Branch of the Facial Nerve

Abstract: The aim of this article is to describe anatomical detail of the course and territory of the horizontal branch of the supraorbital nerve, which connects with temporal branch of the facial nerve. Eighteen hemifaces of Korean cadavers (11 male, 7 female) fixed in 10% formaldehyde solution were dissected. All 18 specimens had horizontal branch of the supraorbital nerve. The horizontal branch emerges out of the supraorbital foramen, runs upward about 12 mm, and then turns laterally at an angle of 104.7 degrees towa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 4 publications
1
15
0
Order By: Relevance
“…Schäfer and Thane (1903) reported a connection between the facial nerve and the supraorbital nerve, a connection that has since been confirmed by various others (Duke‐Elder,1961; Baumel,1974; Hwang et al,2005). In their study on Korean cadavers, Hwang et al (2005) reported that the horizontal branch of the supraorbital nerve is in touch with the temporal branch of the facial nerve and that there are actual connections between them in 44% of cases. Schäfer and Thane (1903) and Duke‐Elder (1961) reported a connection between the horizontal branch of the supraorbital nerve and temporal branch of the facial nerve as well.…”
Section: Introductionmentioning
confidence: 80%
“…Schäfer and Thane (1903) reported a connection between the facial nerve and the supraorbital nerve, a connection that has since been confirmed by various others (Duke‐Elder,1961; Baumel,1974; Hwang et al,2005). In their study on Korean cadavers, Hwang et al (2005) reported that the horizontal branch of the supraorbital nerve is in touch with the temporal branch of the facial nerve and that there are actual connections between them in 44% of cases. Schäfer and Thane (1903) and Duke‐Elder (1961) reported a connection between the horizontal branch of the supraorbital nerve and temporal branch of the facial nerve as well.…”
Section: Introductionmentioning
confidence: 80%
“…54 Furthermore, the location of the recipient site aff ects the outcome of sensory recovery: sensation is recovered better in the orofacial region than in the trunk and lower extremities. [55][56][57] We suggest that this eff ect might be partly explained by higher cortical representation of the face. 58 A benefi cial side-eff ect of immunosuppression with tacrolimus is the dose-dependent acceleration of axonal regeneration, as reported previously for limb allografts.…”
Section: Neurological Principles Sensory Nervesmentioning
confidence: 98%
“…3 Coincidentally, the supraorbital nerve and temporal branch of the facial nerve have a common epineurium, but the perineurium separated as well.…”
Section: Discussionmentioning
confidence: 98%